Effectiveness of behavioral parent training program in reducing symptoms of attention deficit hyperactivity disorder among children and parental stress - Zadeh, Majid Darvishi (2012)
The general purpose of this study was to examine the effectiveness of Behavioural Parent Training Program (BPTP) in reducing symptoms among ADHD children and Parental Stress. Specifically, the study examined the effectiveness of BPTP in reducing selected symptoms of ADHD which included: (i) inattention, (ii) hyperactivity, (iii) hyperactivity-impulsivity, (iv) hyperactivity-impulsivity-inattention as total symptoms and (v) Parental Stress. Using an Experiemntal Randomized Pre-test Post-test Control Group Design, sixty parents of ADHD children from an ADHD centre for children with behavioural and emotional disorders in Kermanshah City, Iran, were randomly assigned to experimental and control groups. Each group consisted of 15 pairs of parents. The parenting programme developed by Barkley (1997), was administered in nine 90-minutes sessions over nine weeks with a one-month follow-up session. Treatment outcomes were evaluated by using ADHD Rating Scale-IV: Home Version (DuPaul,1998) and Parental Stress Index /Short Form (PSI/SF) (Abidin, 1995). Additionally,Conners’ Parent Rating Scales-Revised: Short Form (CPRS-R: SF, 1997) was used to evaluate ADHD symptoms not covered by the ADHD Rating Scale-IV. The instruments were completed by the parents in four scheduled administrations, namely at: (i) preintervention, (ii) post-intervention 1, (iii) post-intervention 2, and (iv) follow-up. The results of an independent t-test on ADHD Rating Scale-IV, CPRS-R, and Parental Stress Index (PSI/SF) show no significant differences between the experimental and the control groups at the pre-intervention stage. Two-way repeated measures ANOVA investigating the significance of differences within and between groups of the subscales of the instruments across the four scheduled administrations showed a significant reduction in all four combinations of ADHD symptoms as well as reduction in parental stress as measured by the abovementioned instruments. The results imply that BPTP can be effective in reducing ADHD symptoms in children, reducing parental stress and also other behavioural problems related to ADHD which were also measured by the instruments. The outcome of the study could benefit family counselors, and psychologists, specifically in conducting psycho-educational interventions as a single treatment for parental management of ADHD children.